Wasim - Tutorial Manual - Hess, Tim M. (Cranfield University, 2011)
A case study tutorial for use with the Wasim soil water balance simulation model, based on irrigated potatoes in the UK.
This manual is an output of Project R6879, funded by DFID under the Knowledge and Research (KAR) Programme. The work was undertaken by HR Wallingford and Cranfield University (at Silsoe), with the active participation of the International Waterlogging and Research Institute (IWASRI), Pakistan.
Keywords: Irrigation; Drainage; Salinity; Model; Tutorial